(untitled) (Sport culture, 2026)
The research aimed to design a rehabilitation program using central stabilization exercises and to identify the effect of this program using these exercises. The researcher hypothesized that there would be significant s difference between the pre- and post-test measurements. The experimental method with a single group, using pre- and post-tests, was used as it was suitable for the research problem. The research population was defined as athletes with anterior cruciate ligament injuries following surgical intervention. The sample consisted of (5) injured athletes selected purposively. After defining and testing the research variables, a pilot study was conducted with two of the research sample, followed by pre-testing. Subsequently, the main experiment was implemented for (8) weeks, with three rehabilitation units per week, using tools designed to rehabilitate this injury. Afterward, post-testing was conducted, and it was concluded that the rehabilitation program using central stabilization exercises had a clear effect on knee joint rehabilitation. We recommend the necessity of using diverse methods that contribute to rehabilitation after surgical intervention.